(untitled) (Studia Politica. Romanian Political Science Review, 2025)
The Russian invasion of Ukraine in 2022 had a profound impact on the Republic of Moldova. The aftermath witnessed an unprecedented influx of Ukrainian refugees, a significant rise in inflation, a decline in political stability, and a deepening energy crisis. The root causes of political instability in Moldova are diverse, with issues of identity and memory playing a central role in the nation-building process since the Soviet Union’s collapse. Moldova, situated between its Romanian roots and Russian- Soviet heritage, confronts numerous challenges in reconciling its past and navigating its future. The Russian occupation of its neighboring country has accentuated these challenges, serving as a crucial test for Moldova’s European-oriented government. The response to this new geopolitical reality, however, has led to some measures that intensified ideological divisions within the population, particularly regarding matters of memory and identity. The contested memorial heritage in Moldova was notably evident during the May 9 celebrations, coinciding with Europe Day and Victory Day. While many European Union countries consider Europe Day a peripheral holiday promoting European values, Moldovan politicians and the public are increasingly giving it attention, with a growing belief that it should replace the Soviet-style Victory Day. Using the "struggle" over the significance of May 9 as a case study, this article explores contemporary Moldovan memory politics influenced by the realities of war.